High local failure rates despite high margin‐negative resection rates in a cohort of borderline resectable and locally advanced pancreatic cancer patients treated with stereotactic body radiation therapy following multi‐agent chemotherapy. (10th February 2022) - Hill, Colin; Sehgal, Shuchi; Fu, Wei; Hu, Chen; Reddy, Abhinav; Thompson, Elizabeth; Hacker‐Prietz, Amy; Le, Dung; De Jesus‐Acosta, Ana; Lee, Valerie; Zheng, Lei; Laheru, Daniel A.; et al.
Abstract: Background: Stereotactic body radiation therapy (SBRT) for patients with borderline resectable and locally advanced pancreatic adenocarcinoma (BRPC/LAPC) remains controversial. Herein, we report on surgical, pathologic, and survival outcomes in BRPC/LAPC patients treated at a high‐volume institution with induction chemotherapy (CTX) followed by 5‐fraction SBRT. Methods: BRPC/LAPC patients treated between 2016 and 2019 were retrospectively reviewed. Surgical and pathological outcomes were descriptively characterized. Overall survival (OS) and progression‐free survival (PFS) were analyzed using Cox proportional hazard regression. Locoregional failure and distant failure were analyzed with Fine–Gray competing risk model. Results: Of 155 patients, 91 (59%) had LAPC and 64 (41%) had BRPC. Almost all were treated with induction multi‐agent CTX with either FOLFIRINOX (75%) or gemcitabine and nab‐paclitaxel (24%) for a median duration of 4.0 months (1–18 months). All received SBRT to a median dose of 33 Gy. Among 64 BRPC patients, 50 (78%) underwent resection, of whom 48 (96%) achieved margin‐negative (R0) resection. Among 91 LAPC patients, 57 (63%) underwent resection, of whom 50 (88%) achieved R0 resection. Despite the high R0 rate, 33% of patients experienced locoregional failure, which was a component of 44% of all failures. After SBRT, median OS and PFS were 18.7 and 7.7 months, respectively. After SBRT, 1‐ and 2‐year OS probabilities were 70% and 45%, whereas, from diagnosis, they were 93% and 51%. Conclusions: Although a high proportion of BRPC/LAPC patients treated with induction multi‐agent CTX followed by SBRT successfully achieved R0 resection, locoregional failure remained common, highlighting the need to continue to optimize radiation delivery in this context. Abstract : A high proportion of patients in a modern cohort of BRPC/LAPC patients treated with multi‐agent CTX followed by SBRT became eligible for surgical exploration and resection with 92% achieving a margin‐negative resection. Despite the high rate of R0 resection, 33% of patients experienced locoregional failure, and 44% of all failures included locoregional failure as a component, highlighting the need to continue to optimize radiation delivery in this context.